Confirmation of destruction of salmonellae within murine peritoneal exudate cells by immunocytochemical technique. - Lin, F R (1989)
A procedure was developed with which peritoneal exudate cell (PEC) preparations were fixed in a glutaraldehyde-picric acid mixture, post-fixed with osmium tetroxide, embedded in LR White resin and then stained with immunogold probe. It provided tissue sections showing both well-defined ultrastructures as well as specifically labelled Salmonella O antigens by electron microscopy. Inbred, male C57BL/6 mice were injected intraperitoneally with 2 x 10(7) virulent Salmonella typhimurium. Peritoneal exudate cells were harvested at 16 and 20 hr after infection. Disintegrating intracellular bacteria were identified as salmonellae by the immunogold markers. Deposition of gold particles in the cytoplasm of phagocytes also indicated that intracellular debris contained digested pathogen. This investigation therefore confirms previous findings of the destruction of salmonellae within inflammatory polymorphs and macrophages.